Clinical Application of Whole Exome Sequencing for Monogenic Disorders in PICU of China - Liu, Yingchao; Hao, Chanjuan; Li, Kechun; Hu, Xuyun; Gao, Hengmiao; Zeng, Jiansheng; Guo, Ruolan; Liu, Jun; Guo, Jun; Li, Zheng; Qi, Zhan; Jia, Xinlei; et al. (Frontiers in Genetics, 2021)
Objectives. Whole exome sequencing (WES) has been widely used to detect genetic disorders in critically ill children. Relevant data are lacking in pediatric intensive care units (PICUs) of China. This study aimed to investigate the spectrum of monogenic disorders and the diagnostic yield and clinical utility of WES from a PICU in a large children’s hospital of China. Methods. From July 2017 to February 2020, WES was performed in 169 critically ill children with suspected monogenic diseases in the PICU of Beijing Children’s Hospital. The clinical features, human phenotype ontology terms, and assessment of clinical impact were analyzed. Results. The media age of the enrolled children was 10.5 months (range, 1 month to 14.8 years). After WES, a total of 43 patients (25%) were diagnosed with monogenic disorders. The most common categories of diseases were metabolic disease (33%), neuromuscular disease (19%), and multiple deformities (14%). The diagnosis yield of children with “metabolism/homeostasis disorder” and “growth delay” or “ocular anomalies” was higher than that of children without these features. In addition, the diagnosis rate increased when more features were observed in children. The results of WES had an impact on the treatment for 30 cases (70%): (1) change of treatment (n=11), (2) disease monitoring initiation (n=18), (3) other systemic evaluation (n=3), (4) family intervention (n=2), and (5) rehabilitation and redirection of care toward palliative care (n=12). Conclusion. WES can be used as an effective diagnostic tool in the PICU of China and has an important impact on the treatment of patients with suspected monogenic conditions.